Diagnostic and prognostic markers in gliomas – an update. (June 2013) - Ma, R.; de Pennington, N.; Hofer, M.; Blesing, C.; Stacey, R.
Abstract Gliomas are the most common primary central nervous system tumour seen in adults. There have been many advances over the last two decades as we widen our search for a molecular basis of gliomagenesis. Many biomarkers have been discovered to be important in the management of gliomas, including 1p19q co-deletion, MGMT promoter methylation, BRAF and IDH1 mutations. In this review, we attempt to summarise the available literature on these biomarkers and their use in the diagnosis and management of gliomas. We pay special attention to the recently discovered IDH1 mutation, which is already proving to be a valuable new marker for favourable prognosis and may also indicate a greater response to therapy. 1p19q co-deletions have been shown to delineate a clinically distinct tumour type and are now routinely tested for in certain situations and can help direct treatment. MGMT promoter methylation is one of the most commonly studied biomarkers in gliomas. It has been shown to be a strong positive prognostic marker in gliomas, with positive tumours being more sensitive to chemotherapy. However, a lack of alternatives means that it is not yet a routine mutation tested for clinically. BRAF mutations are new markers found in pilocytic astrocytomas. Although the prognostic value of such mutations is not yet known, they may play a significant role in the diagnosis and treatment of such tumours. IDH1 mutations are 'the new kid on the block' and seem to play a central role in the pathogenesis of gliomas. They represent an independent and favourable prognostic marker and are a new molecular marker for disease diagnosis. Its role in determining response to chemotherapy is still controversial but with further study, IDH1 mutations may prove to be an invaluable marker in the management of gliomas.